WEAR RESISTANCE OF POLYMER COMPOSITE MATERIALS FOR PLANE SPHERICAL BEARINGS - Khimko, Margaryta; Khimko, Andrii; Mnatsakanov, Rudolf; Klipachenko, Vladyslav; Makarenko, Ruslan (Problems of Friction and Wear, 2024)
The use of polymer composite materials allows significantly reduce the labor intensity of manufacturing friction unit parts due to high-performance and economical resources. According to the definition, a composite material consists of one or more continuous phases of a homogeneous matrix with one or more dispersive phases. In this regard, the reliable operation of metal-polymer tribosystems primarily depends on the structural and morphological factor influencing the tribomechanical characteristics of materials. The principle of producing composite materials consists of a pre-created combination of two different phases (fillers and matrix) using certain technological techniques. As a result of filling, materials are obtained whose physical and mechanical properties differ from the matrix. The choice of fillers for metal-polymer materials depends on the purpose of the material, the need to change some tribomechanical characteristics and the type of polymer matrix. Plain spherical bearings with metal-polymer tribosystems are very popular in the aviation industry. They are made from stainless and corrosion-resistant steels and do not require maintenance. Compacts have an extremely high payload-to-weight ratio and are used in primary and secondary flight control systems. They have a hinged type design. The work identifies modern antifriction composite materials for use in plain spherical bearings. The structures and wear resistance characteristics of polymer materials under special operating conditions - vibration, reverse movements - have been determined. It has been established that the design of the composite material is of paramount importance under increased loads in low-frequency vibration tests. It has been determined that the Fluroglide material, consisting of carbon fibers with the addition of PTFE material with functional additives, shows high tribological characteristics comparable to classic metal fluoroplastic tape. At extreme loads of metal-polymer composite materials, a key role is played by relaxation processes and the ability of the base of the composite material to restrain polymer materials and fillers from crushing and from the action of reverse movements. Under these critical operating conditions, Fluroglide exhibits superior wear resistance to metal fluoroplastic tape.